2022
DOI: 10.3389/fcimb.2022.907519
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cohorts of Aspergillus fumigatus Transcription Factors Are Required for Epithelial Damage Occurring via Contact- or Soluble Effector-Mediated Mechanisms

Abstract: Damage to the lung epithelium is a unifying feature of disease caused by the saprophytic fungus Aspergillus fumigatus. However, the mechanistic basis and the regulatory control of such damage is poorly characterized. Previous studies have identified A. fumigatus mediated pathogenesis as occurring at early (≤ 16 hours) or late (>16 hours) phases of the fungal interaction with epithelial cells, and respectively involve direct contact with the host cell or the action of soluble factors produced by mature f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Other vital functions of hyphae-secreted GAG are mediating neutrophil apoptosis and resistance to neutrophil extracellular traps (NETs), modulating host immune responses through platelet activation, inducing secretion of IL-1 receptor antagonists, and inflammasome activation [31,73,75]. Therefore, GAG is critical for host damage and fungal virulence, as studies in mouse models of invasive pulmonary aspergillosis (IPA) have shown, where GAG-deficient strains exhibit reduced adherence to lung epithelial cells, do not form biofilms, and are less virulent [7,32]. The multiple and important functions of GAG in virulence have prompted the study of the mechanisms involved in its biosynthesis.…”
Section: Galactosaminogalactanmentioning
confidence: 99%
See 1 more Smart Citation
“…Other vital functions of hyphae-secreted GAG are mediating neutrophil apoptosis and resistance to neutrophil extracellular traps (NETs), modulating host immune responses through platelet activation, inducing secretion of IL-1 receptor antagonists, and inflammasome activation [31,73,75]. Therefore, GAG is critical for host damage and fungal virulence, as studies in mouse models of invasive pulmonary aspergillosis (IPA) have shown, where GAG-deficient strains exhibit reduced adherence to lung epithelial cells, do not form biofilms, and are less virulent [7,32]. The multiple and important functions of GAG in virulence have prompted the study of the mechanisms involved in its biosynthesis.…”
Section: Galactosaminogalactanmentioning
confidence: 99%
“…The pathogenesis of the disease mediated by A. fumigatus occurs in a multi-step manner and involves the morphological transition of the inhaled fungal spore to a hyphae form. Epithelial damage can be considered to occur in the early (conidia) or late (hyphae) phase of the fungal interaction with epithelial cells [7]. In healthy immunocompetent individuals, the growth of hyphae is impeded by immune mechanisms, whereas, in people with immune deterioration, such as those who have leukemia or who have undergone bone marrow or solid organ transplantation, mycelial development leads to severe disease, which can be lifethreatening (Figure 2) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Growth rates specific to a fungal morphology (morphology-specific growth rates), such as germination rates of fungal spores or proliferation rates of hyphae, can be estimated from morphology-specific growth data to evaluate morphology-specific changes in fungal growth over time. For example, hyphal extension rates have been derived from hyphal microscopy data to investigate hyphae-specific growth defects in mutant strains of Aspergillus fumigatus [ 22 ]. Such morphology-specific growth rates can also be estimated from mechanistic models of fungal growth fit to directly measured time-course data.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have calculated fungal growth rates to quantitatively evaluate temporal changes in fungal growth in different experimental conditions [22][23][24][25]. Growth rates specific to a fungal morphology (morphology-specific growth rates), such as germination rates of fungal spores or proliferation rates of hyphae, can be estimated from morphology-specific growth data to evaluate morphology-specific changes in fungal growth over time.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identify that the zinc-finger C 2 H 2 type transcription factor (TF) SltA is functionally linked to the control of germination as it has a non-redundant role in controlling emergence from dormancy, germ tube formation and temporal and spacial control of hyphal branching. The ∆ sltA strain was recently studied for virulence and showed a reduced capacity to adhere to, invade, and damage pulmonary epithelial cells ( 16 , 17 ). Additionally, ∆ sltA showed increased susceptibility to cell membrane stressors ( 16 ).…”
Section: Introductionmentioning
confidence: 99%